Dose Response of Acute ATP Supplementation on Strength Training Performance - dos Santos Nunes de Moura, Helton Pereira; Jäger, Ralf; Purpura, Martin; Rathmacher, John A.; Fuller, John C.; Rossi, Fabrício E. (Frontiers in Sports and Active Living, 2021)
Background: Chronic oral ATP supplementation benefits cardiovascular health, muscular performance, body composition, and recovery while attenuating muscle breakdown and fatigue. A single 400mg dose of oral ATP supplementation improved lower body resistance training performance and energy expenditure in recreational resistance trained males, however, the minimal effective dose is currently unknown. Materials and Methods Twenty recreationally trained men (age 28.6±1.0 years, body mass 81.2 ±2.0kg, height 175.2±1.4cm, 1RM 141.5 ±5.0kg) consumed a single dose of either 400mg, 200mg, or 100mg ATP (PEAK ATP®, TSI USA LLC, Missoula, MT, USA) or a placebo in a randomized, placebo-controlled crossover design, separated by a one week wash out between treatments. After warm-up, participants performed 4 sets of half-squats using free-weights until movement failure separated by 2 minutes of rest between sets. Results In comparison to placebo, 400mg ATP significantly increased the number of set 1 repetitions (+13%, p=0.04), and numerically increased total repetitions (+7%, p=0.19) and total weight lifted (+6%, p=0.22). 200mg ATP numerically increased set 1 repetitions (+4% p=0.47), while 100mg ATP showed no improvements over placebo. 100mg ATP (-4%, p<0.05) and 400mg ATP (-4%, p=0.11) decreased the perceived rate of exertion compared to placebo Conclusions In this study, the effective minimal dose of acute oral ATP supplementation during resistance exercise to increase performance was determined to be 400mg, while as little as 100mg showed improvements in perceived exertion.